Implementasi Trilogi Kepemimpinan dan Nilai Budi Pekerti dalam Pembelajaran Abad ke-21 - Safitri, Wahyuni Dwi (CV. Kurnia Grup, 2025)
This article examines the importance of building character education for students in elementary schools in the 21st century through Tamansiswa teachings in the form of the Leadership Trilogy and moral values. In the midst of the increasingly rapid flow of globalization and technological developments, education is not only required to develop intellectual intelligence, but education is also required to form a good personality in accordance with moral values. The concept of character education according to Ki Hadjar Dewantara is rooted in humanitarian values, emphasizing the formation of individuals who are able to think critically, independently, and have social awareness. The implementation of the Leadership Trilogy which reads Ing Ngarsa Sung Tuladha (in front giving examples and role models), Ing Madya Mangun Karsa (in the middle building enthusiasm), Tut Wuri Handayani (in the back giving motivation or encouragement). Provides guidance for teachers in creating a conducive learning atmosphere and motivating students. The application of moral values which include: responsibility, discipline and honesty, compassion and tolerance, simplicity, independence, and mutual cooperation, is carried out through classroom learning activities and real examples from teachers. Despite challenges in its implementation, such as lack of understanding from educators and environmental support, the Leadership Trilogy is considered relevant in preparing students to have 21st century skills (critical thinking, communication, collaboration, and creativity) in facing future challenges.